Brahui Rubai in Rakhshan - Sabir, Ghulam Dastagir; Baloch, Manzoor (Makhz (Research Journal), 2023)
Rubai, an esteemed genre in poetry, traces its origins to Persian literature in Iran. Scholars attribute its inception to the eminent Persian poet Abul Hassan Rodaki. Over time, Arab poets also embraced this form to express their emotions. As the centuries unfolded, rubai gained popularity across various languages worldwide. Notably, rubai found a receptive audience in the languages of the Indian subcontinent. Among these, the Brahui language stands as one of the oldest. Despite its ancient roots, Brahui poets initially grappled with the intricate structure and rhythmic demands of rubai. It wasn’t until the mid-2000s that this genre began to flourish in Brahui poetry. The Rakhshan region of Balochistan played a pivotal role in nurturing remarkable rubai compositions in the Brahui language. A quarterly magazine called Chirag, published in four languages from the main city of Rakhshan, Nushki, emerged as a significant catalyst for promoting Brahui rubai. Ali Saqi, a leading Brahui poet from Rakhshan, holds the distinction of compiling the first collection of Rubaiyyat in Brahui. His poetry anthology titled Janoon e Saqi showcases a rich tapestry of Brahui rubaiyyat. Additionally, Saqi’s eagerly awaited second book, Deewan e Rubaiyyat, promises further exploration of this poetic form. Other representative poets from Rakhshan, such as Dr. Alam Akhbi, Imaran Fariq, and Sheikh Atiq Hasrat, have also contributed to the rubai tradition. Meanwhile, a new generation of poets—Zahid Salam, Basit Mahr, Javed Sakir, Ibrahim Abrar, Dad Muhammad, and Jawad—continue to experiment with this genre. In summary, the quarterly magazine Chirag and the poets of Rakhshan have played a pivotal role in elevating rubai within the Brahui language, weaving a poetic legacy that bridges cultures and generations